Reaching for veterinary pharmacy services: an overlooked routine by community pharmacists? - Dias, Rita (2022)
Objectives Community pharmacists claim veterinary pharmacy as an integral part of their duties. There a paucity of studies investigating medication and health products’ dispensation for veterinary purposes. This study aimed to probe the Portuguese community pharmacists’ knowledge and behaviour towards veterinary pharmacy practice. Methods A cross-sectional exploratory survey, using an online questionnaire, was sent to a sample of academic-related community pharmacists in greater Lisbon, Portugal (N = 349). The questionnaire addressed participants’ specific education and training, counselling of products, and attitudes towards veterinary prescriptions. Logistic regression was used to estimated participants’ propensity for changing veterinary prescriptions independently. Everyday case scenarios were used to ascertain veterinary pharmacotherapy knowledge. Key Findings Participation reached 57.6% (N = 201), pointing to the theme’s relevance, with 83.6% females and a mean age of 36 years (SD =10.1). A large proportion (71.6%) declared to have received veterinary pharmacy education, although virtually all pharmacists (99.0%) perceived a skills deficit. The overall level of correct decisions regarding case scenarios reached 54%, although most professionals counsel pets’ treatments (85.6%). 18% of the sample declared to have changed a prescription without contacting the veterinarian. The propensity to independent medication changes was associated with being a male pharmacist, having one to two decades of professional experience, and working in community pharmacies with a permanent supply of prescribed veterinary pharmaceuticals. Conclusions Although recognizing limitations in veterinary pharmacy competencies, not all community pharmacists decide to minimize potential hazards to animals’ health as with human health. Present findings reinforce the urgency of further formal education and interprofessional collaboration.